Concentration Level of the Banking Industry in CEE Countries - Barjaktarović, Lidija; Filipović, Sanja; Dimić, Maja (Industrija, 2013)
The purpose of the paper work is to determine on the basis of empirical research, if there is a relation between the level of concentration and competitiveness within banking sector of chosen countries of Central and Eastern Europe (CEE): Serbia, Croatia, Bosnia and Herzegovina, Montenegro, Macedonia, Bulgaria, Romania, Hungary and Albania. The level of concentration is measured by applying the concentration ratio of five big banks (CR5) and Herfindal-Hirschman index (HH index) in the period from 2007 to 2012 for the following banks’ balance items: assets, approved loans and collected deposits. On the basis of received results, the research shows that there is no relation between the level of concentration and level of competitiveness. Furthermore, it is approved that banking market of analyzed CEE countries is moderate to high concentrated in accordance with CR5 (values of index are in the range of 46% to 85% for mentioned three banks’ indicators), i.e. no market concentration to moderate concentration accordingly to HHI (values of index are in the range of 559 to 2070 points).